A Proposed Model for M-Banking Adoption - Abdulkadir, Nurudeen (2010)
The evolution of powerful and versatile information systems have altered the way business transactions are made. Millions of dollars are spent by organizations in developing and maintaining these technologies in quest of gaining competitive edge. This cherished goal can only be realized if the target market adopt and use these technologies. Technologies such as Automated Teller Machine (ATM), internet banking, and mobile banking have now become a prerequisite in the banking business. This study extends the applicability of TAM and TPB constructs to investigate the significant factors influencing users' adoption of m-banking services in Universiti Utara Malaysia. The research model was empirically tested through a questionnaire of 125 respondents. Findings showed that perceived usefulness and social influence have significant impact on mobile banking adoption. In contrast with previous studies, perceived ease of use, perceived credibility, image, perceived financial cost, and computer/internet experience were not significant in explaining mobile banking adoption. In summary, perceived usefulness contributed the most in explaining mobile banking adoption. The research findings have both practical and theoretical implications. Practically, the study is hoped to serve as a useful insight for banks and system developers in developing and deploying mobile banking systems that are in consonance with the needs of the target customers. Theoretically, the study extends to the body of literature in mobile banking adoption.